Optimizing Promotion and Service Quality in Influencing Purchase Decisions in the Tourism Sector: A Study on Wuki Travel Jogja - Hari Rachmadi; Fuadi Afif; Hermadistha Dheanova (Politeknik Pariwisata NHI Bandung, 2024)
This research examines the influence of promotion and service quality on purchase decisions for tourism products at Wuki Travel Jogja. Using a quantitative approach, a survey was conducted with 100 respondents who had previously used Wuki Travel Jogja's services. The study employed various analytical techniques, including validity and reliability testing, as well as multiple regression analysis to examine the impact of the independent variables (promotion and service quality) on the dependent variable (purchase decision). The results indicate that both promotion and service quality have a significant and positive influence on purchase decisions when analyzed simultaneously. However, when analyzed separately, promotion was found to have a more dominant effect, with a coefficient value of 0.897, compared to service quality, which showed no significant impact. The study concludes that improving promotional strategies may have the most substantial effect on influencing customer purchase decisions, while service quality, though important, may not play as significant a role in isolation